Income inequality and rule of law in Bulgaria - Buba, Saad; Ishak, Suryati (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study presents evidence about the relationship between income inequality and the quality of rule of law Bulgaria. Rule of law in Bulgaria has been in negative index for the past two decades. This study uses an autoregressive distributed lag (ARDL) model to test the co-integration and long-run relationships between these two variables, with rule of law as the dependent variable. The results of the co-integration bounds test showed that the variables are co-integrated, but the findings on the long-run coefficients showed no expressive relationship between income inequality and rule of law even in the short-run, as for the case in Bulgaria.